1963
DOI: 10.1002/ar.1091470108
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the rectal (salt‐secreting) gland of the spiny dogfish, Squalus acanthias

Abstract: The rectal gland of the spiny dogfish, Squalus acanthias has been described by light and electron microscopy. The cell outline shows remarkable complexity in electron micrographs. The basal plasma membrane has numerous complex infoIdings and interdigitations separated by groups of mitochondria. The lateral plasma membrane also shows extensive interdigitation. The apical region demonstrates profiles of interleafing cell processes with much membrane interdigitation occurring between them but containing few mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

1965
1965
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 43 publications
3
24
0
1
Order By: Relevance
“…Immunolocalization of PLMS and Na,K-ATPase ␣-SubunitThe rectal gland is composed of winding tubules formed by tall columnar cells arranged around a central duct or lumen as previously described (45)(46)(47). The luminal cell surface exhibits only a few small microvilli (Fig.…”
Section: Cloning and Sequencing Of Plms-the Initial Squalusmentioning
confidence: 87%
“…Immunolocalization of PLMS and Na,K-ATPase ␣-SubunitThe rectal gland is composed of winding tubules formed by tall columnar cells arranged around a central duct or lumen as previously described (45)(46)(47). The luminal cell surface exhibits only a few small microvilli (Fig.…”
Section: Cloning and Sequencing Of Plms-the Initial Squalusmentioning
confidence: 87%
“…The fine structure of the stria vascularis has been observed in various mammals by many authors (ENGSTROM, SJOSTRAND and SPOENDLIN, 1955;SMITH, 1957;CHOU, 1961;YAMAMOTO and NAKAI, 1964;RODRIGUEZ-ECHANDIA and BURGOS, 1965;HINOJOSA and RODRIGUEZ-ECHANDIA, 1966 active transport of ions has been reported in salt secreting cells (DOYLE, 1960;BULGER, 1963;PHILPOTT and TEMPLETON, 1964) and in chloride cells (PHILPOTT and COPELAND, 1963;CONTE, 1969). In the cochlear duct, RODRIGUEZ-ECHANDIA and BURGOS (1965) have suggested that the unusually high concentration of potassium ions in the endolymph is due to the presence cf a specialized structure somewhere in the stria vascularis for secretion of this ion.…”
Section: Discussionmentioning
confidence: 91%
“…Similar structural specialization of cell surface has been reported in the epithelium of the salivary glands (SCOTT and PEASE 1959, others), of the sweat gland (HIBBS 1958, others), and of urinary tubules which are well known to be involved in the vigorous water transport (PEASE 1956). Furthermore, it is known that some salt-secreting cells in the lower vertebrates also show similar specialization of lateral surface (DOYLE 1960, BULGER 1963. Recently SOROKIN (1965) has described in the bronchial gland of opossum the hydrotic cell, the lateral surfaces of which are provided with the extensive cytoplasmic folds similar to those of nasal glandular cell.…”
Section: Discussionmentioning
confidence: 99%